Effect of Tween 20 on the Electrochemical Synthesis and Properties of Nickel Hydroxide Nanoparticles - Pramana, Yanatra Budi; Asranudin; Budipramana, Krisyanti (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Nickel (II) hydroxide (Ni(OH)₂) nanoparticles have attracted significant research interest due to their potential in applications such as supercapacitors, batteries, and electrocatalysis. However, conventional synthesis methods often face challenges related to high costs and complex instrumentation. This study presents a simple, low-cost, and controllable approach for synthesizing Ni(OH)₂ nanoparticles using a surfactant-assisted electrochemical method. The synthesis was conducted through electrolysis at 100°C in an aqueous solution containing sodium citrate, with Tween 20 employed as a structure-directing agent, Tween 20 was effective in producing smaller, dispersed, quasi-spherical particles while preventing severe agglomeration. The resulting nanoparticles were characterized using various analytical techniques, including UV-Vis and FTIR spectroscopy, X-ray Diffraction (XRD), Thermal Gravimetric Analysis (TGA), and electron microscopy (TEM/SEM). UV-Vis analysis showed a characteristic absorption peak at 387 nm, confirming nanoparticle formation. XRD analysis validated the synthesis of a nanocrystalline hexagonal Ni(OH)₂ phase. Electron microscopy revealed a hierarchical, flower-like morphology composed of nanosheets and demonstrated that Tween 20 was effective in producing smaller, dispersed, quasi-spherical particles while preventing severe agglomeration. Furthermore, the thermal decomposition of Ni(OH)₂ into highly crystalline cubic, NiO via calcination was confirmed by TGA, XRD, and FTIR analyses, with the main decomposition occurring at approximately 335°C. This research demonstrates an effective and economical route for producing Ni(OH)₂ nanoparticles with controlled morphology, enhancing their potential for practical applications.